Búsqueda de salud y oferta de sanación. Estudio teológico de caso: Parroquia «Natividad del Señor» (Rosario, Argentina) - Virginia Raquel Azcuy (Franciscanum, 2020)
Attention is focussed in this contribution on the spontaneous attraction by large multitudes to the Catholic parish «Nativity of the Lord» in the city of Rosario, Argentina, were people come seeking health for themselves and/or for relatives. This phenomenon shows one of the main motivations tied to current religious beliefs and practices in Argentina, especially but not exclusively among middle-and lower-class groups. Why this parish has become particularly inviting has to do with the charismatic figure of its parish priest, Ignacio Peries, originally from Sri Lanka, in charge of the parish since the beginnings of the 1980s. The offer of healing that distinguishes this community holds this Srilankan priest as a central character, even though he is accompanied by several male and female assistants, as well as numerous volunteers receiving the thousands of visitors who arrive each weekend. Key element inthe healing ritual offered by this parish acting as a sanctuary movement is the priest’s blessing of sick people and their relatives, after celebration of the Mass (which is almost always presided by him as well). This presentation offers an interdisciplinary framework for understanding this phenomenon; it looks theologically at it from the voices of its actors; and it proposes lines for further reflecting on popular spirituality in the religious field, particularly regarding diversity of beliefs and healthcare.